2010
DOI: 10.1096/fj.10-163261
|View full text |Cite
|
Sign up to set email alerts
|

The calcium ATPase SERCA2 regulates desmoplakin dynamics and intercellular adhesive strength through modulation of PKCα signaling

Abstract: Darier's disease (DD) is an inherited autosomal-dominant skin disorder characterized histologically by loss of adhesion between keratinocytes. DD is typically caused by mutations in sarcoendoplasmic reticulum Ca(2+)-ATPase isoform 2 (SERCA2), a major regulator of intracellular Ca(2+) homeostasis in the skin. However, a defined role for SERCA2 in regulating intercellular adhesion remains poorly understood. We found that diminution of SERCA2 function by pharmacological inhibition or siRNA silencing in multiple h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 53 publications
6
67
1
Order By: Relevance
“…Plakophilin 2, which regulates intercellular junction assembly, is a crucial scaffold for PKCa (Bass-Zubek et al, 2008). PKCa signaling also regulates the dynamics of desmoplakin through the Ca 2+ ATPase SERCA2 (also known as ATP2A2), which stabilizes desmosomes (Hobbs et al, 2011). However, plakoglobin, which is structurally related to b-catenin, can be phosphorylated at both tyrosines and serines (Gaudry et al, 2001;Shibamoto et al, 1994).…”
Section: Late Intermediate State Of Emtmentioning
confidence: 99%
“…Plakophilin 2, which regulates intercellular junction assembly, is a crucial scaffold for PKCa (Bass-Zubek et al, 2008). PKCa signaling also regulates the dynamics of desmoplakin through the Ca 2+ ATPase SERCA2 (also known as ATP2A2), which stabilizes desmosomes (Hobbs et al, 2011). However, plakoglobin, which is structurally related to b-catenin, can be phosphorylated at both tyrosines and serines (Gaudry et al, 2001;Shibamoto et al, 1994).…”
Section: Late Intermediate State Of Emtmentioning
confidence: 99%
“…Desmogleins (DSG1-4) and desmocollins (DSC1-3) are cadherin superfamily proteins located in desmosomes. Previous studies have demonstrated that desmosomes are affected by calcium influx into the cell (28) and that homophilic and heterophilic interactions between DSC and DSG proteins generate cell aggregation (29,30). It has also been shown that desmosomal protein expression may be altered during cancer development (31,32) and may regulate cell proliferation (33).…”
Section: Desmosomal Proteins Also Coordinate Cell Aggregationmentioning
confidence: 99%
“…In terms of this concept, it is of great interest to note, as the fi rst step of PV-affected desmosome remodeling, that PV-IgG activates PKC , which is located at desmosomal plaques when activated (Garrod et al, 2005) and can alter the stable hyper-adhesive desmosomes to dynamic weak-adhesive desmosomes (Sharpe et al, 1989;Hobbs et al, 2011). These PKC-dependent events lead keratinocytes to become more sensitive to blistering processes, that is, depletion and non-assembly of Dsg3 in desmosomes (Figure 4).…”
Section: Dynamic Weak-adhesive Desmosomes: a Prerequisite For Dsg Depmentioning
confidence: 99%